Evidence on ergogenic action of glucocorticoids as a doping agent risk - Duclos, M. (The Physician and Sportsmedicine, 2010)
Systemic administration of glucocorticoids (GCs) is banned by the World Anti-Doping Agency (WADA) during competition. Few studies have examined the effects of GCs on exercise performance, but increasing evidence has shown that short-term GC intake enhances performance in animals and humans. However, there are many health risks associated with GC use. Based on the available evidence, as presented in this article, I conclude that GCs are doping agents and should remain on the WADA`s list of banned products. Because of the complexity of GCs, however, determining the boundaries between their medical use and abuse (eg, in sports) is a constant challenge for the WADA.